Comparison of bone temperature elevation in drilling of human, bovine and porcine bone - Mohd Faizal, Ali Akhbar; A. R., Yusoff (Elsevier B.V., 2019)
This paper compares the maximum temperature elevation in human, bovine and porcine bone corresponding to the drilling rotational speed from 1,000 to 10,000 rev/min. For this purpose, we perform drilling simulation using human, bovine and porcine bone models combined with experimental validation process. We demonstrate numerically and experimentally that bovine bone can mimic the human bone in terms of temperature elevation in bone drilling (0.49 – 1.15% error). The increasing rotational speed gives rise to the maximum bone temperature. The results indicate that the drilling simulation can be used to approximate the reasonably accurate output in biomedical research.